2001
DOI: 10.1002/cne.1097
|View full text |Cite
|
Sign up to set email alerts
|

Immunotoxic destruction of distinct catecholamine subgroups produces selective impairment of glucoregulatory responses and neuronal activation

Abstract: The toxin-antibody complex anti-d(beta)h-saporin (DSAP) selectively destroys d(beta)h-containing catecholamine neurons. To test the role of specific catecholamine neurons in glucoregulatory feeding and adrenal medullary secretion, we injected DSAP, unconjugated saporin (SAP), or saline bilaterally into the paraventricular nucleus of the hypothalamus (PVH) or spinal cord (T2-T4) and subsequently tested rats for 2-deoxy-D-glucose (2DG)-induced feeding and blood glucose responses. Injections of DSAP into the PVH … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

28
294
1
1

Year Published

2002
2002
2011
2011

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 246 publications
(324 citation statements)
references
References 80 publications
28
294
1
1
Order By: Relevance
“…In addition, injections of 5-thio-glucose in different hypothalamic nuclei failed to induce a glucoregulatory response, whereas its injection into the NTS and the basolateral medulla region containing the A1/C1 catecholaminergic neurons, which project to different sites of the hypothalamus, induced a strong response. [54][55][56] Also, in decerebrated rats, the hyperglycemic response to an intraperitoneal injection of 2-DG is preserved, 57 and c-fos immunostaining revealed that the activated neurons are present in the NTS, the dorsal motor nucleus of the vagus and the catecholaminergic neurons of the basolateral medulla. 58 Thus, hypoglycemia can be detected at several sites, the hepatoportal vein area, the brainstem and the hypothalamus.…”
Section: S64mentioning
confidence: 95%
See 1 more Smart Citation
“…In addition, injections of 5-thio-glucose in different hypothalamic nuclei failed to induce a glucoregulatory response, whereas its injection into the NTS and the basolateral medulla region containing the A1/C1 catecholaminergic neurons, which project to different sites of the hypothalamus, induced a strong response. [54][55][56] Also, in decerebrated rats, the hyperglycemic response to an intraperitoneal injection of 2-DG is preserved, 57 and c-fos immunostaining revealed that the activated neurons are present in the NTS, the dorsal motor nucleus of the vagus and the catecholaminergic neurons of the basolateral medulla. 58 Thus, hypoglycemia can be detected at several sites, the hepatoportal vein area, the brainstem and the hypothalamus.…”
Section: S64mentioning
confidence: 95%
“…Furthermore, food intake can be stimulated by direct injections of 5-thio-glucose into the basolateral medulla, the dorsal motor nucleus of the vagus and the NTS, 54 where glucose-sensitive catecholaminergic neurons are located, which project to the hypothalamus, in particular the PVN and the AN. 55,58 Immunotoxin destruction of these neurons showed their role in the feeding response to the 2-DG glucoprivic signal 56 and in the regulation of NPY and Agrp expression. 55 A role for central Glut2 expression in feeding regulation has been suggested by experiments in which its expression was decreased by the injection of antisense oligonucleotides in the AN.…”
Section: Feeding Controlmentioning
confidence: 99%
“…Establishing these linkages requires, in part, identifying afferents signaling the PVH during glycemic challenge and the neurotransmitter(s) involved in such signaling. Ritter et al (2001) identified an essential afferent pathway by showing that selectively destroying PVH afferents originating from hindbrain CA cell groups impaired the feeding and PVH responses to 2-DG or insulin challenges (elevated CRH hnRNA, Fos mRNA, and circulating corticosterone) but not those occurring basally or from forced-swim challenge (Ritter et al, 2003). These lesions also impair PVH phospho-ERK1/2 responses to insulin (Rapp et al, 2006).…”
Section: Phospho-erk1/2 Tracks Crh Neuron Activation During Glycemic mentioning
confidence: 99%
“…Thus, for example, Ob-Rb is coexpressed with AgRP in arcuate neurons, whereas the caudal brainstem contains no AgRP perikarya. Similarly, research indicates (38,147,149) that glucose interoceptors are coextensive with, or coexpressed within, norepinephrine and epinephrine neurons in the DVC and VLM, whereas cell bodies for these catecholamines are not found in forebrain. Determination of the neurotransmitter phenotypes of the neurons sensitive to blood-borne correlates of metabolic state begins the discussion taken up in the next section, addressing the transmission of interoceptive information to other substrates, nearby and distant, involved in energy balance.…”
Section: Glucose Sensorsmentioning
confidence: 99%
“…Biogenic amine neurons, therefore, represent an element in a pathway, endemic to the caudal brainstem, with potent effects on ingestive behavior. Under physiological conditions, these neurons may receive signals arising from brainstem interoceptors (33,147,205). But because of direct and indirect descending pathways from hypothalamus to these neurons, a possibly critical role for basal forebrain interoceptors or integrative mechanisms can never be ruled out.…”
Section: Neurochemical Mediationmentioning
confidence: 99%